2010
DOI: 10.1007/s10753-010-9233-0
|View full text |Cite
|
Sign up to set email alerts
|

Possible Protective Role of Chloramphenicol in TSST-1 and Coagulase-Positive Staphylococcus aureus-Induced Septic Arthritis with Altered Levels of Inflammatory Mediators

Abstract: Chloramphenicol is mostly used against coagulase-negative Staphylococcus aureus, and its protective role against coagulase-positive S. aureus is not well studied. In our study, arthritis was induced in mice by S. aureus (Apollo Gleneagles 33 (AG-33) or American Type Culture Collection 25923 (ATCC-25923)) infection. Chloramphenicol was administered after 2 h of infection. Mice were killed at 1, 3, 5 days post-infection. Mice inoculated with pathogenic Staphylococci (AG-33) expressing coagulase and Toxic shock s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The rate of change in absorbance was measured spectrophotometrically at 405 nm. MPO enzyme activity has been defined as the concentration of enzyme degrading 1 μ m of peroxide/min at 37 °C and was expressed as change in absorbance/min/mg of protein .…”
Section: Methodsmentioning
confidence: 99%
“…The rate of change in absorbance was measured spectrophotometrically at 405 nm. MPO enzyme activity has been defined as the concentration of enzyme degrading 1 μ m of peroxide/min at 37 °C and was expressed as change in absorbance/min/mg of protein .…”
Section: Methodsmentioning
confidence: 99%
“…Quinupristin-dalfopristin decreased the concentration of pro-inflammatory cell wall components (lipoteichoic acid and teichoic acid) and TNF activity in cerebrospinal fluid compared to the ceftriaxone-treated rabbits [57]. A previous report showed that chloramphenicol, a member of the phenicols group, elevated the IL-10 levels, a potent anti-inflammatory cytokine [58].…”
Section: Lincosamides Streptogramins and Phenicolsmentioning
confidence: 89%
“…The incidence of the rash was lower in the CHL-PRED versus the CHL arm; however, the difference was not significant, potentially due to the limited size of our cohort. CHL is an antibacterial agent, which offers good coverage of most S. aureus infection strains and also bears anti-inflammatory properties [28][29][30], and PRED is a non-fluorinated low-potency steroid, with an anti-inflammatory effect. In our clinical practice, we indeed observe a marked improvement in a fraction of the patients with active EGFRI-induced papulopustular rash, using this combination.…”
Section: Discussionmentioning
confidence: 99%
“…Chloramphenicol (CHL) is an antibacterial agent with some anti-inflammatory properties, [28][29][30], and prednisolone (PRED) is a low-potency steroid, with an anti-inflammatory effect. As the pathophysiology of the papulopustular rash is inflammatory [31][32][33], a combination of these agents seemed a promising prophylactic option.…”
Section: Introductionmentioning
confidence: 99%